Communities of Ruin: Humanitarian Violence and the Amazon's Uncontacted Tribes. Issue 1 (2nd January 2017) - Bouchard, Danielle
ABSTRACT: This essay investigates portrayals of 'uncontacted tribes' of the Amazon by the humanitarian organisations and the popular texts that aim to study and save them. These portrayals rely upon a convergence of figures of racial, gender and sexual deviance recuperated from the age of high imperialism, with newer configurations of the human which emerged in the wake of the Second World War. How might we account for the fact that these objects of preservation are presented – save for a few crucial exceptions – as degraded, almost dead or simply not there? By way of addressing this question, I offer the production of the 'uncontacted' as one site for examining the imbrication of humanitarianism and violence.